2023
DOI: 10.3390/su15032037
|View full text |Cite
|
Sign up to set email alerts
|

Research on How Executive Connections Affect Enterprise Digital Transformation: Empirical Evidence from China

Abstract: In the context of the digital economy, the external connection of executives provides enterprises with a good idea to amplify their potential for digital transformation with the help of external forces. Therefore, we conduct a theoretical exploration and an empirical analysis of the relationship between executive connections and enterprise digital transformation. As the research sample, we use the A-share manufacturing companies listed in China from 2012 to 2021. According to sufficient verifications, we disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Upon testing H1 , it is found that corporate CEO discretion significantly facilitates digital transformation. The main factors influencing digital transformation are financial asset allocation, stability of the executive team, director linkages, financing methods, R&D expenditure, and firm financialisation [ [58] , [59] , [60] , [61] , [62] , [63] ]. Li and Rui argue that the stewardship theory applies to China's real enterprises, and CEO discretionary power shows a significant negative relationship with corporate financialisation [ 64 ].…”
Section: Discussion Of Influence Mechanismmentioning
confidence: 99%
“…Upon testing H1 , it is found that corporate CEO discretion significantly facilitates digital transformation. The main factors influencing digital transformation are financial asset allocation, stability of the executive team, director linkages, financing methods, R&D expenditure, and firm financialisation [ [58] , [59] , [60] , [61] , [62] , [63] ]. Li and Rui argue that the stewardship theory applies to China's real enterprises, and CEO discretionary power shows a significant negative relationship with corporate financialisation [ 64 ].…”
Section: Discussion Of Influence Mechanismmentioning
confidence: 99%
“…As it takes some time from when municipal party secretaries take office to when they have a real impact on the economic development of the prefecture-level city in which they are located, if a new municipal party secretary takes office from January to June of the current year, the current year is defined as the change year; otherwise, the next year is defined as the change year. The results in Columns (7) and (8) of Table 14 demonstrate that the absolute values of Rel_PC regression coefficients are higher for the samples in which municipal party secretaries changed in the year during which firms are at the prefecture level than for the samples without a change in the number of municipal party secretaries, indicating that a change in the number of municipal party secretaries increases the inhibitory effect of political connections on corporate DT.…”
Section: City Secretary Replacementmentioning
confidence: 98%
“…Many enterprises facing resource constraints seek to build political connections in the DT process [ 6 ]. On one hand, political connections can help enterprises reduce political uncertainty, enabling them to obtain substantial support in information, technology, talent, funding, and other aspects during the DT process and achieving strategy and resource sharing among enterprises [ 7 , 8 ]. On the other hand, the decision-making behavior of enterprises with close political connections is also more susceptible to government influence, participating more in nonproductive activities, weakening corporate performance, and possibly not fully achieving optimal resource allocation [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although it is the most commonly applied in the UK with many cases are available through Jisc, there remains little peer-reviewed published research into the way it has been applied (see Foster et al ., 2023). Evidence does, however, highlight how an organisation’s climate for shared decision-making influences how employees voluntarily contribute or share new ideas during digital transformation (Haskasap et al ., 2023) and how executives' business, technical and financial connections can support (or otherwise) digital transformation efforts (Bai et al ., 2023). This evidence highlights it is reasonable to expect variations in the engagement of the framework in higher education, partly depending on its fit with existing cultures and the style of the that engagement over time (also see Huber et al ., 2023).…”
Section: Reflections On Applicationmentioning
confidence: 99%